Implementasi Program Pengelolaan Bank Sampah Dalam Mewujudkan Masyarakat Sadar Lingkungan di Wilayah Ring Satu PT Pertamina (Persero) Fuel Rewulu - Afry Rakhmadany; Duta Wahyu Wijaya; Zulfikar Busmark Assegaf; Dela Ayu Puspita Dewi (UIN Siber Syekh Nurjati Cirebon, 2021)
Garbage, both organic and non-norganic, is still a problem for the environment. Garbage is generally caused by increasing population and mobility which has an impact on human consumptions, if this problem could not be handled, the waste will cause certain impacts such as polluting rivers and air due to the way people treat waste. Therefore, it is necessary to have waste management from the firth where the waste is produced. As an effort to increase public awareness about waste management in order to protect the environment. the CSR Pertamina Fuel Rewulu and the community are trying to form the Watu Berkah Argomulyo waste bank. This study aims to describe CSR efforts in empowering the community through waste banks, how to manage waste banks and the impact of the existence of waste banks on public awareness in managing waste. This study uses descriptive qualitative methods to produce informative and valid data, data collection techniques using interviews and field observations. Sources of data were obtained from sources from waste bank managers, companies and the community. The data is then analyzed interactively by collecting, reducing, presenting and drawing the conclusions. The results of the study show that through the stages and strategies of empowerment, Pertamina Fuel Rewulu CSR realizes efforts to create public awareness about good waste management through waste bank programs and education that is carried out both directly and waste bank managers who have been given strengthening and insight about the waste banks.